The Value of Corpus Callosum Measurement in the Diagnosis of Cerebral Atrophy - Ji-Ping, Zhao; Chun-Xiao, Cui; Chong-Feng, Duan; Lei, Niu; Xue-Jun, Liu (Current Medical Imaging, 2020)
Objective: The study aimed to investigate the relationship between the corpus callosum area (CCa) and the degree of cerebral atrophy in patients with cerebral atrophy. Methods: 119 patients with brain atrophy were grouped according to the degree of brain atrophy. Median sagittal CCa and intracranial area (ICa) were measured, and the ratio of corpus callosum to the intracranial area (CCa-ICa ratio) was calculated. The data were analyzed using ANOVA. Results: CCa significantly reduced in patients with cerebral atrophy, and the degree of cerebral atrophy was found to be positively correlated with the degree of reduction in the CCa. Conclusion: The reduction in the CCa and the CCa-ICa ratio in the median sagittal can be used as a reference indicator for the diagnosis and grading of brain atrophy in clinical practice.
Keywords: cerebral atrophy